2014
DOI: 10.1016/j.yhbeh.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity, endogenous reproductive hormones and ovulation in premenopausal women

Abstract: We investigated whether sexual activity was associated with reproductive function in the BioCycle Study, a prospective cohort study that followed 259 regularly menstruating women aged 18 to 44 years for one (n=9) or two (n=250) menstrual cycles in 2005–2007. Women were not attempting pregnancy nor using hormonal contraceptives. History of ever having been sexually active was assessed at baseline and frequency of sexual activity, defined as vaginal-penile intercourse, was self-reported daily throughout the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…In the present sample, T levels were not significantly higher in women who were frequently active: in fact, it was lower. Other studies have similarly found lower T in women who are highly vs. infrequently sexually active (Prasad et al, 2014). Taken together, these findings suggest that the effect of T on the immune system is as a relative signal: when baseline T is low (e.g., as in highly sexually active women), the T response to sexual activity would be relatively high, triggering an immunosuppressive response.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the present sample, T levels were not significantly higher in women who were frequently active: in fact, it was lower. Other studies have similarly found lower T in women who are highly vs. infrequently sexually active (Prasad et al, 2014). Taken together, these findings suggest that the effect of T on the immune system is as a relative signal: when baseline T is low (e.g., as in highly sexually active women), the T response to sexual activity would be relatively high, triggering an immunosuppressive response.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, sexually active and abstinent women differ in patterns of E2 and P4 across the menstrual cycle (Prasad et al, 2014). Although we confirmed all women in the present sample had an LH surge (a marker of ovulation), the sexually active women in this sample did have significantly higher luteal-phase P4 than did the sexually abstinent women (see (Lorenz et al, 2015b) for more details).…”
Section: Methodsmentioning
confidence: 99%
“…Most notably, several studies have suggested that sexually active women have significantly higher estrogen and luteal-phase progesterone than do abstinent women [4649]; given the powerful immune effects of ovarian hormones, it is reasonable to suspect the effects reported here are at least partially mediated by endocrine mechanisms. However, given the complex patterns of immune effects (e.g., different patterns in condom users vs. non-users), the effects of sexual activity are likely not driven solely by hormonal differences.…”
Section: Discussionmentioning
confidence: 93%
“…Given significant differences between sexually active and inactive women in estradiol (E2) and P4 across the cycle (82), it is possible that endocrine factors play a role. Both E2 and P4 have immune effects, with the former thought to be generally anti-inflammatory (with notable exceptions (83)) and the latter thought to be generally pro-inflammatory, particularly within the female reproductive tract (84).…”
Section: Discussionmentioning
confidence: 99%